S92 Impact of posture on diaphragm morphology assessed using upright MRI – healthy volunteer experience. (December 2018) - Safavi, S; Arthofer, C; Cooper, A; Alenazi, S; Gowland, P; Bolton, C; Prayle, A; Hall, IP
Abstract : Introduction: The diaphragm is the most important respiratory muscle, and dysfunction causes significant symptoms including breathlessness. Under diagnosis of abnormal diaphragm movement is a clinical problem. Pulmonary function tests and ultrasound are the main diagnostic tools used but these may be insensitive to pathology. Aim: To assess the impact of posture on diaphragm morphology in adult healthy volunteers using an upright MRI system. Method: Healthy volunteers with no history of respiratory disease or smoking were recruited. Spirometry was performed in upright and supine positions. Repeated MR images were acquired with a 0.5T Paramed Upright scanner in upright and supine positions during breath-holds at end-inspiration and end-expiration. Images were obtained in coronal and sagittal planes. Each scan was repeated three times to assesses within-subject reproducibility. The shape, excursion, and curvature of the diaphragm were estimated with a semi-automated method on Matlab after spatial alignment. Intra-observer reproducibility was assessed by analysing the images on two separate occasion, a week apart. Results: 14 healthy volunteers (4 females), aged 23–38 years, were scanned. No significant postural change in FVC was noted. Posture did not impact the diaphragm morphology either. As expected, MRI detected a significant change between expiration and inspiration in healthy volunteers (p=0.0004). The technique was reproducible within subjects. Intra-observer reproducibility was also demonstrated. Conclusion: This healthy study supports the use of upright MRI system for assessing postural changes in diaphragm morphology. The next step is to assess its use in patients with diaphragmatic pathology and respiratory disease that impairs diaphragm function, such as COPD with hyperinflation.